Correction: Efficient and stable electrorheological fluids based on chestnut-like cobalt hydroxide coupled with surface-functionalized carbon dots. Issue 20 (11th May 2022) - Liang, Yudai; Liu, Yihao; Zhou, Yaozhong; Shi, Quan; Zhang, Mengying; Li, Yancheng; Wen, Weijia; Feng, Lingyan; Wu, Jinbo
Abstract : Correction for 'Efficient and stable electrorheological fluids based on chestnut-like cobalt hydroxide coupled with surface-functionalized carbon dots' by Yudai Liang et al., Soft Matter, 2022, DOI: ; 10.1039/D2SM00176D .